Efficient flame-retardant porous ceramic and preparation method thereof
By using a mixture of polydimethyl silicone oil and polydimethyl silicone rubber, modified nanosilica and starch silica fibers in porous ceramics, a multi-layer structure of high-efficiency flame-retardant porous ceramics are formed, which solves the problems of aging of existing materials and insufficient flame retardant performance, and achieves high strength, high porosity and high flame retardancy.
Patent Information
- Application Number
- CN202411694132.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
Existing building insulation materials are prone to aging under the alternation of hot and cold, rainwater and air, have a low lifespan, and are not at high flame retardant enough. Porous ceramics can prevent the spread of flames under high temperature conditions, but they are difficult to meet the requirements of high porosity and high strength.
By mixing polydimethyl silicone oil with polydimethyl silicone rubber, an organic precursor is formed; immersing organic-inorganic mixed fibers into a modified nanosilica solution to form a porous reinforcement; using starch @silica fibers as the first bonding system to form a ceramic-silica fiber composite; then using organic precursors as the second bonding system to fix the nodes, improve the bonding strength and porosity of the fiber framework to form an efficient flame-retardant porous ceramic.
Porous ceramics with high strength, high porosity and high flame retardancy are achieved, which improves the high temperature stability and mechanical properties of the material, and enhances the flame retardant performance and toughening.
Smart Images

Figure BDA0005151713130000121 
Figure BDA0005151713130000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a highly efficient flame-retardant porous ceramic and a preparation method thereof. Background Art
[0002] Building insulation materials are used to reduce the heat dissipation from indoor buildings to the outside by taking measures on the building's external envelope structure, thereby maintaining the indoor temperature of the building. Building insulation materials play an important role in creating a suitable indoor thermal environment and saving energy in building insulation. In the prior art, building exterior walls mostly use extruded polystyrene boards, molded polystyrene boards, polyurethane foam boards and other materials to ensure energy conservation and thermal insulation of the wall. Although such materials have good thermal insulation performance, they are very easy to age under the combined effects of alternating cold and hot, rain, air, etc., and have a short lifespan. In addition, the flame retardant performance of such materials is not high enough.
[0003] Porous ceramics are a new type of ceramic material, often with a porosity of more than 50%, and can be used in fields such as construction, chemical industry, and metallurgy. Porous ceramics maintain the characteristics of polymer materials at room temperature, and can quickly ceramicize under high temperature conditions. They can be self-supporting and form porous ceramic-like materials with a certain strength. They can effectively prevent the spread of flames under high temperature conditions, and can also absorb heat to a certain extent. They have certain flame retardant properties and high-temperature thermal protection. Among them, the porosity of porous ceramics is inversely proportional to its strength. The more micropores in the material and the more evenly distributed they are, the higher the strength of the material. How to meet the high porosity and high strength of porous ceramics has become the focus of porous ceramic research.
[0004] Existing fiber-based porous ceramics are mainly composed of fibers and binders between fibers. The most common binder at present is silica sol solution, which has a serious thermal migration effect. That is, the silica sol at the node will quickly migrate to the outer surface of the fiber matrix as the water evaporates during the heat treatment process, causing the node to fail and unable to fix the overlap of the matrix, resulting in greatly weakened mechanical properties. In addition, the silica sol solution will transform into amorphous silicon oxide at high temperature. During the migration process, the amorphous silicon oxide will fill the internal pores of the fiber-based porous ceramics and reduce the porosity of the porous ceramics. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a highly efficient flame-retardant porous ceramic, which can prepare a porous ceramic with high strength, high porosity and high flame retardancy.
[0006] Another object of the present invention is to provide a high-efficiency flame-retardant porous ceramic, which is prepared by the above-mentioned preparation method of the high-efficiency flame-retardant porous ceramic.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, a method for preparing a highly efficient flame-retardant porous ceramic is provided, comprising the following steps:
[0009] S1, mixing polydimethylsilicone oil and polydimethylsilicone rubber to obtain an organic precursor;
[0010] S2, immersing the organic-inorganic hybrid fiber in a solution containing modified nano-silicon dioxide to obtain a porous reinforcement;
[0011] S3, adding ceramic fiber to a dispersion system to form a ceramic slurry, wherein the dispersion system includes a dispersant, a flame retardant and starch@silicon oxide fiber; then dispersing the porous reinforcement into the ceramic slurry, and then adding the porous reinforcement into an organic precursor for ultrasonic homogenization to obtain a mixed slurry;
[0012] S4. Inject the mixed slurry into a mold, vacuum filter, and dry to obtain a ceramic body. Sinter the ceramic body in a high-temperature furnace and cool naturally to obtain a highly efficient flame-retardant porous ceramic.
[0013] In a second aspect, a high-efficiency flame-retardant porous ceramic is provided, which is made by the preparation method of the high-efficiency flame-retardant porous ceramic.
[0014] The technical solution of the present invention has at least the following advantages and beneficial effects:
[0015] In the present invention, starch@silica fiber solution is used as the first bonding system, a ceramic-silica fiber complex is formed by in-situ curing of starch, a preliminary fiber skeleton is formed by alternating overlapping of ceramic fibers and silica fibers, and a large number of pores are formed between the fibers. An organic precursor is used as the second bonding system, and the cross-linking and curing of the organic precursor is used to overlap and fix nodes between the ceramic-silica fiber complex and the porous reinforcement, and the fiber matrix is stabilized by the nodes, thereby improving the bonding strength between the porous reinforcement and the fiber complex, increasing the porosity of the fiber skeleton, forming a stable reinforced fiber skeleton, and improving the high temperature stability and mechanical properties of the fiber skeleton. By adding a flame retardant, the porous ceramic can be toughened while improving the flame retardancy of the porous ceramic, which is beneficial to improving the flame retardancy and mechanical properties of the porous ceramic.
[0016] The ceramic-silicon oxide fiber composite and the porous reinforcement are connected by an organic precursor to form a multilayer structure including a ceramic-silicon oxide fiber composite layer, a porous interface layer and an organic-inorganic hybrid fiber layer. The fibers of the inner and outer layers are interlaced to improve the interfacial bonding strength between the layers and enhance the stability of the fiber skeleton. During the mixing process, starch will also enter the porous interface layer and the organic-inorganic hybrid fiber layer through the pore channels between the layers, further improving the bonding strength between the layers. Vacuum filtration can remove excess organic precursors inside the fiber skeleton except for the nodes to avoid the accumulation of binders in the pores.
[0017] During the sintering process, on the one hand, the starch expands, promotes the arrangement of the fibers, and improves the compactness of the fiber skeleton. As the sintering proceeds, the starch turns into gas and is discharged, forming a large number of macropores inside the material, allowing different pore structures to be formed in each layer, so that the porous ceramic has multi-level pores and improves the porosity. On the other hand, the organic precursor cross-linked product undergoes a cracking reaction and forms a stable and firm silicon oxide crystal phase. At this time, the binder's wrapping of the fiber increases, enhancing the stability of the lap joint, making the fiber skeleton firm and stable. When the material is stressed, the stress can be effectively transmitted through the nodes and the fiber surface, showing a greater compressive strength and further enhancing the mechanical properties. At the same time, the binder of the lap joint can be made tighter, the pore wall thinner, and the pore diameter larger, further increasing the porosity. DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0019] A method for preparing a highly efficient flame-retardant porous ceramic comprises the following steps:
[0020] S1, mixing polydimethylsilicone oil and polydimethylsilicone rubber to obtain an organic precursor;
[0021] S2, immersing the organic-inorganic hybrid fiber in a solution containing modified nano-silicon dioxide to obtain a porous reinforcement;
[0022] S3, adding ceramic fiber to a dispersion system to form a ceramic slurry, wherein the dispersion system includes a dispersant, a flame retardant and starch@silicon oxide fiber; then dispersing the porous reinforcement into the ceramic slurry, and then adding it to an organic precursor for ultrasonic homogenization to obtain a mixed slurry;
[0023] S4. Inject the mixed slurry into a mold, vacuum filter, and dry to obtain a ceramic body. Sinter the ceramic body in a high-temperature furnace and cool naturally to obtain a highly efficient flame-retardant porous ceramic.
[0024] Since the silica sol solution itself has a serious thermal migration effect and will transform into amorphous silicon oxide at high temperature, the amorphous silicon oxide will fill the internal pores of the fiber-based porous ceramics during the migration process and reduce the porosity of the porous ceramics.
[0025] The inventor loads starch on silica fiber to form starch @ silica fiber as the first bonding system. First, the ceramic fiber and silica fiber are connected by the room temperature bonding effect of starch, and the ceramic fiber and silica fiber are alternately overlapped to form a preliminary fiber skeleton, and a large number of pores are formed between the fibers. Secondly, the silica fiber will melt during sintering, and the in-situ melting of the silica fiber is used to react with the adjacent ceramic fiber and organic-inorganic hybrid fiber, and the ceramic fiber and the organic-inorganic hybrid fiber are further bonded together, that is, the bonding between the ceramic fiber and the porous reinforcement is enhanced, and the fiber matrix strength is improved. At the same time, the melting and disappearance of the silica fiber will also provide a large number of holes to a certain extent, which will improve the ceramic porosity. The organic precursor is used as the second bonding system, and the cross-linking and curing of the organic precursor is used to overlap and fix the nodes between the ceramic-silica fiber complex and the porous reinforcement. The fiber matrix is stabilized by the node, the bonding strength between the porous reinforcement and the fiber complex is improved, the porosity of the fiber skeleton is increased, and a stable enhanced fiber skeleton is formed, which improves the high temperature stability and mechanical properties of the fiber skeleton.
[0026] The ceramic-silicon oxide fiber composite and the porous reinforcement are connected through an organic precursor to form a multilayer structure including a ceramic-silicon oxide fiber composite layer, a porous interface layer and an organic-inorganic hybrid fiber layer. The interlacing of the fibers of the inner and outer layers improves the interface bonding strength between the layers and enhances the stability of the fiber skeleton. During the mixing process, the starch will also enter the porous interface layer and the organic-inorganic hybrid fiber layer through the pore channels between the layers, further improving the bonding strength between the layers.
[0027] By adding flame retardants, the porous ceramics can be toughened while improving the flame retardant properties, which is beneficial to improving the comprehensive properties of the porous ceramics.
[0028] Since nano-silicon dioxide has a very small particle size and a large number of various hydroxyl groups on its surface, it is polar and highly hydrophilic. Many particles are linked to each other in chains, and the chain structures interact with each other through hydrogen bonds to form a three-dimensional network structure composed of aggregates. In this three-dimensional network structure, the intermolecular force is very strong, and it is extremely difficult to disperse evenly during the mixing process with organic-inorganic hybrid fibers, which affects the uniformity of the material's pores.
[0029] The inventors modified nano-silica, weakened its surface polarity, and reduced its surface energy state, so as to improve the compatibility and bonding force between nano-silica and fibers, and at the same time improve the porosity of nano-silica. Using modified nano-silica as a matrix and organic-inorganic hybrid fibers as a reinforcing agent to prepare a porous reinforcement, the modified nano-silica is loaded on the organic-inorganic hybrid fibers. On the one hand, the problem of modified nano-silica dispersion can be further solved; on the other hand, a porous interface layer can be formed on the surface of the hybrid fibers to improve the porosity; thirdly, the material strength can be enhanced.
[0030] Vacuum filtration can remove excess organic precursors from the fiber skeleton except for the nodes, avoiding the accumulation of binders in the pores. It mainly discharges the uncross-linked small molecules in the organic precursors, generally polydimethylsilicone oil, to avoid the violent cracking reaction of small molecules during the sintering process, the overflow of small molecules and the production of a large amount of amorphous silica, which accumulates on the surface of the sample and causes the sample to crack and the structure to collapse.
[0031] During the sintering process, on the one hand, the starch expands, promotes the arrangement of the fibers, and improves the compactness of the fiber skeleton. As the sintering proceeds, the starch turns into gas and is discharged, forming a large number of macropores inside the material, allowing different pore structures to be formed in each layer, so that the porous ceramic has multi-level pores and improves the porosity. On the other hand, the organic precursor cross-linked product undergoes a cracking reaction and forms a stable and firm silicon oxide crystal phase. At this time, the binder's wrapping of the fiber increases, enhancing the stability of the lap joint, making the fiber skeleton firm and stable. When the material is stressed, the stress can be effectively transmitted through the nodes and the fiber surface, showing a greater compressive strength and further enhancing the mechanical properties. At the same time, the binder of the lap joint can be made tighter, the pore wall thinner, and the pore diameter larger, further increasing the porosity.
[0032] In this embodiment, the mass ratio of polydimethylsilicone oil to polydimethylsilicone rubber is 2-4: 1. The two cross-link and solidify at room temperature to form an organic precursor. Polydimethylsilicone oil can also reduce the viscosity of the organic precursor to help improve the dispersion effect of the fiber. It also has a good lubrication effect, which is convenient for subsequent ceramic body demoulding.
[0033] In this embodiment, the organic-inorganic hybrid fiber includes alumina fiber and nylon fiber in a mass ratio of 2:1. The alumina fiber improves the fiber matrix strength through the combined effects of fiber-matrix interface debonding, fiber breakage and fiber bridging. During the sintering process, adjacent sintered particles undergo diffusion mass transfer, the surfaces bond to each other and form sintering necks. As the temperature increases and the time increases, the sintering necks between the particles continue to thicken until a dense body is formed. The pores remaining after oxidation and burnout of nylon fibers are not completely closed due to their large size, and gradually spheroidize inside the ceramic core to form nearly circular closed pores. Alumina fibers are interspersed between multiple sintered particles and cannot be densely stacked with the sintered particles, leaving a large number of pores to form connected pores, thereby increasing the porosity of porous ceramics.
[0034] In this embodiment, the preparation process of modified nano-silica includes: a. preparing porous nano-silica using nano-silica; b. preparing modified nano-silica by composite modification of porous nano-silica particles using a coupling agent and a surfactant.
[0035] In this embodiment, in step a, the preparation method of porous nano-silica is as follows: grinding and mixing nano-silica powder and silica aerogel on a ball mill for 2 hours, then adding water glass to the mixed powder for uniform rolling, drying at 100-120° C. for 20-24 hours, and then heat treating at 950° C. for 3 hours. Silica aerogel has low density and high porosity. By treating nano-silica with silica aerogel, the micropore content of nano-silica can be increased, and nano-silica can also be toughened and reinforced, thereby improving the strength of nano-silica while ensuring that the nano-silica has a high porosity.
[0036] In this embodiment, in step b, the coupling agent is a silane coupling agent or a titanate coupling agent, and the surfactant is sodium dodecyl sulfate or sodium hexametaphosphate.
[0037] In this embodiment, the mass ratio of the dispersant, the flame retardant and the starch@silicon oxide fiber in the dispersion system is 1:2:4. The dispersant is hydroxypropyl methylcellulose, and the flame retardant is one or more of magnesium hydroxide, aluminum hydroxide and graphite.
[0038] In the implementation manner of this embodiment, the preparation method of starch@silicon oxide fiber is: add starch to water, heat to 50-60°C, stir and mix to obtain a suspension, add silicon oxide fiber to the suspension, and stir for 20-30 minutes. This can improve the uniformity and loading rate of starch on silicon oxide fiber.
[0039] In a second aspect, a high-efficiency flame-retardant porous ceramic is provided, which is made by the preparation method of the high-efficiency flame-retardant porous ceramic.
[0040] Example 1
[0041] A method for preparing a highly efficient flame-retardant porous ceramic comprises the following steps:
[0042] S1, mixing polydimethylsilicone oil and polydimethylsilicone rubber in a ratio of 2:1 to obtain an organic precursor;
[0043] S2, immersing the organic-inorganic hybrid fiber (alumina fiber and nylon fiber in a mass ratio of 2:1) in a solution containing modified nano-silicon dioxide, stirring for 30 minutes, and drying to obtain a porous reinforcement;
[0044] S3, adding ceramic fiber to a dispersion system to form a ceramic slurry, wherein the dispersion system includes a dispersant (hydroxypropyl methylcellulose), a flame retardant (magnesium hydroxide) and starch@silicon oxide fiber in a mass ratio of 1:2:4; then dispersing the porous reinforcement into the ceramic slurry, and then adding it to an organic precursor for ultrasonic homogenization to obtain a mixed slurry;
[0045] S4. Inject the mixed slurry into a mold, vacuum filter, and dry to obtain a ceramic body. Sinter the ceramic body in a high-temperature furnace and cool naturally to obtain a highly efficient flame-retardant porous ceramic.
[0046] The preparation process of modified nano-silica includes: a. Preparing porous nano-silica using nano-silica: grinding and mixing nano-silica powder and silica aerogel on a ball mill for 2 hours, then adding water glass to the mixed powder and rolling it evenly, drying it at 100°C for 20 hours, and then heat treating it at 950°C for 3 hours; b. Composite modification of porous nano-silica particles with a coupling agent (KH-570) and a surfactant (sodium dodecyl sulfate) to prepare modified nano-silica.
[0047] The preparation method of starch@silicon oxide fiber is as follows: adding starch into water, heating to 50° C., stirring and mixing to obtain a suspension, adding silicon oxide fiber into the suspension, and stirring for 20 minutes.
[0048] Example 2
[0049] A method for preparing a highly efficient flame-retardant porous ceramic comprises the following steps:
[0050] S1, mixing polydimethylsilicone oil and polydimethylsilicone rubber in a ratio of 3:1 to obtain an organic precursor;
[0051] S2, immersing the organic-inorganic hybrid fiber (alumina fiber and nylon fiber in a mass ratio of 2:1) in a solution containing modified nano-silicon dioxide, stirring for 35 minutes, and drying to obtain a porous reinforcement;
[0052] S3, adding ceramic fiber to a dispersion system to form a ceramic slurry, wherein the dispersion system includes a dispersant (hydroxypropyl methylcellulose), a flame retardant (aluminum hydroxide) and starch@silicon oxide fiber in a mass ratio of 1:2:4; then dispersing the porous reinforcement into the ceramic slurry, and then adding it to an organic precursor for ultrasonic homogenization to obtain a mixed slurry;
[0053] S4. Inject the mixed slurry into a mold, vacuum filter, and dry to obtain a ceramic body. Sinter the ceramic body in a high-temperature furnace and cool naturally to obtain a highly efficient flame-retardant porous ceramic.
[0054] The preparation process of modified nano-silica includes: a. Preparing porous nano-silica using nano-silica: grinding and mixing nano-silica powder and silica aerogel on a ball mill for 2 hours, then adding water glass to the mixed powder and rolling it evenly, drying it at 105°C for 21 hours, and then heat treating it at 950°C for 3 hours; b. Composite modification of porous nano-silica particles with a coupling agent (NDZ-130) and a surfactant (sodium hexametaphosphate) to prepare modified nano-silica.
[0055] The preparation method of starch@silicon oxide fiber is as follows: adding starch into water, heating to 55° C., stirring and mixing to obtain a suspension, adding silicon oxide fiber into the suspension, and stirring for 25 minutes.
[0056] Example 3
[0057] A method for preparing a highly efficient flame-retardant porous ceramic comprises the following steps:
[0058] S1, mixing polydimethylsilicone oil and polydimethylsilicone rubber in a ratio of 4:1 to obtain an organic precursor;
[0059] S2, immersing the organic-inorganic hybrid fiber (alumina fiber and nylon fiber in a mass ratio of 2:1) in a solution containing modified nano-silicon dioxide, stirring for 40 minutes, and drying to obtain a porous reinforcement;
[0060] S3, adding ceramic fiber to a dispersion system to form a ceramic slurry, wherein the dispersion system includes a dispersant (hydroxypropyl methylcellulose), a flame retardant (graphite) and starch@silicon oxide fiber in a mass ratio of 1:2:4; then dispersing the porous reinforcement into the ceramic slurry, and then adding it to an organic precursor for ultrasonic homogenization to obtain a mixed slurry;
[0061] S4. Inject the mixed slurry into a mold, vacuum filter, and dry to obtain a ceramic body. Sinter the ceramic body in a high-temperature furnace and cool naturally to obtain a highly efficient flame-retardant porous ceramic.
[0062] The preparation process of modified nano-silica includes: a. Preparing porous nano-silica using nano-silica: grinding and mixing nano-silica powder and silica aerogel on a ball mill for 2 hours, then adding water glass to the mixed powder and rolling it evenly, drying it at 120°C for 24 hours, and then heat treating it at 950°C for 3 hours; b. Composite modification of porous nano-silica particles with a coupling agent (KH-570) and a surfactant (sodium dodecyl sulfate) to prepare modified nano-silica.
[0063] The preparation method of starch@silicon oxide fiber is as follows: adding starch into water, heating to 60° C., stirring and mixing to obtain a suspension, adding silicon oxide fiber into the suspension, and stirring for 30 minutes.
[0064] Comparative Example 1
[0065] In this comparative example, no organic precursor was used.
[0066] Comparative Example 2
[0067] Starch@silica fiber was not used in this comparative example.
[0068] Comparative Example 3
[0069] In this comparative example, no porous reinforcement was used.
[0070] Comparative Example 4
[0071] In this comparative example, the nano-silicon dioxide was not modified.
[0072] Comparative Example 5
[0073] In this comparative example, the porous reinforcement is only organic-inorganic hybrid fibers.
[0074] Comparative Example 6
[0075] In this comparative example, the porous reinforcement is only modified nano-silica.
[0076] Comparative Example 7
[0077] In the dispersion system of this comparative example, starch@silicon oxide fiber is replaced by starch.
[0078] Comparative Example 8
[0079] In the dispersion system of this comparative example, starch@silicon oxide fiber is replaced by silicon oxide fiber.
[0080] Comparative Example 9
[0081] In this comparative example, the organic-inorganic hybrid fibers were replaced with alumina fibers.
[0082] Test Case
[0083] The high-efficiency flame-retardant porous ceramics of the embodiment and the comparative example were tested. The porosity, flexural strength and compressive strength were tested according to GB / T16533-1996 "General Technical Requirements for Porous Ceramic Products" as the test standard, and the flame retardant performance was tested by the vertical combustion method. The results are as follows:
[0084] Table 1
[0085]
[0086]
[0087] According to Table 1, compared with the comparative example, the high-efficiency flame-retardant porous ceramics of the embodiment have higher porosity, lower thermal conductivity, higher flexural strength and compressive strength, and better flame retardant properties. Compared with Example 1, Comparative Examples 1-2 show that starch@silicon oxide fiber is used as the first bonding system and the organic precursor is used as the second bonding system. The combination of the two binders can improve the porosity of the ceramic and enhance the strength of the ceramic. Compared with Example 1, Comparative Example 3 shows that the porous reinforcement can improve the porosity and strength of the ceramic. Compared with Example 1, Comparative Examples 4-6 show that the modification of nano-silicon dioxide and the modification of organic-inorganic hybrid fibers with modified nano-silicon dioxide can enhance the performance of the porous reinforcement and make the porous ceramics have better porosity and strength. Compared with Example 1, Comparative Examples 7-8 show that the synergistic combination of starch and silicon oxide fibers can improve the porosity and strength of porous ceramics. Compared with Example 1, Comparative Example 9 shows that the organic-inorganic hybrid fiber composite has a better effect on improving the performance of porous ceramics.
[0088] In summary, the method for preparing the high-efficiency flame-retardant porous ceramic provided by the present invention can prepare porous ceramics with high strength, high porosity and high flame retardancy.
[0089] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly efficient flame-retardant porous ceramic, characterized in that: The following steps are involved: S1, mixing polydimethylsilicone oil and polydimethylsilicone rubber to obtain an organic precursor; S2, immersing the organic-inorganic hybrid fiber in a solution containing modified nano-silicon dioxide to obtain a porous reinforcement; S3, adding ceramic fiber to a dispersion system to form a ceramic slurry, wherein the dispersion system includes a dispersant, a flame retardant and starch@silicon oxide fiber; then dispersing the porous reinforcement into the ceramic slurry, and then adding the porous reinforcement into an organic precursor for ultrasonic homogenization to obtain a mixed slurry; S4. Inject the mixed slurry into a mold, vacuum filter, and dry to obtain a ceramic body. Sinter the ceramic body in a high-temperature furnace and cool naturally to obtain a highly efficient flame-retardant porous ceramic.
2. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 1, characterized in that: The mass ratio of the polydimethylsilicone oil to the polydimethylsilicone rubber is 2-4:
1.
3. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 1, characterized in that: The organic-inorganic hybrid fibers include alumina fibers and nylon fibers in a mass ratio of 2:
1.
4. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 1, characterized in that: The preparation process of the modified nano-silicon dioxide comprises: a. preparing porous nano-silicon dioxide by using nano-silicon dioxide; b. preparing modified nano-silicon dioxide by composite modification of porous nano-silicon dioxide particles by using a coupling agent and a surfactant.
5. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 4, characterized in that: In step a, the preparation method of the porous nano-silica is: grinding and mixing nano-silica powder and silica aerogel on a ball mill for 2 hours, then adding water glass to the mixed powder and rolling it evenly, drying it at 100-120° C. for 20-24 hours, and then heat treating it at 950° C. for 3 hours.
6. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 4, characterized in that: In step b, the coupling agent is a silane coupling agent or a titanate coupling agent, and the surfactant is sodium dodecyl sulfate or sodium hexametaphosphate.
7. The method for preparing a highly efficient flame-retardant porous ceramic according to any one of claims 1 to 6, characterized in that: The preparation method of the starch@silicon oxide fiber is as follows: adding starch into water, heating to 50-60° C., stirring and mixing to obtain a suspension, adding the silicon oxide fiber into the suspension, and stirring for 20-30 minutes.
8. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 7, characterized in that: The mass ratio of the dispersant, the flame retardant and the starch@silicon oxide fiber in the dispersion system is 1:2:
4.
9. The method for preparing a highly efficient flame-retardant porous ceramic according to claim 7, characterized in that: The dispersant is hydroxypropyl methylcellulose, and the flame retardant is one or more of magnesium hydroxide, aluminum hydroxide and graphite.
10. A high-efficiency flame-retardant porous ceramic made by the preparation method of the high-efficiency flame-retardant porous ceramic as described in any one of claims 1 to 9.
Citation Information
Cited By
Porous nanofiber-based elastic ceramic flocculus product as well as preparation method and application thereof
CN122518524A